An Efficient Stocking Strategy for Grazing Replacement Heifers - Keith R. Harmoney; John R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2020)
Even though Kansas native rangelands often have steep slopes or shallow soils not conducive to many other uses other than livestock grazing, native rangeland and perennial grassland acres in Kansas have been declining. Cropland acreage over this same time frame has increased, and rangelands have also become more fragmented by small ranchettes and urbanization. Producers may be looking to increase production efficiency on a shrinking forage land base. The use of intensive early stocking (IES) is one of the most efficient stocking strategies to produce beef on rangeland acres. The IES strategy has been widely used in eastern Kansas and is capable of increasing beef production by 30–40% compared to continuous season long stocking (SLS). In western Kansas, IES and continuous SLS have resulted in similar beef production. However, a modified IES (MIES) system, which combines greater early season animal density on high-quality forage of IES and late season individual animal selectivity for a high-quality diet of SLS, has increased beef production by 26% compared to continuous SLS alone on western Kansas rangelands. Even with this significant increase in production efficiency, stocker production is largely overshadowed by cow/calf production in terms of acres grazed in western Kansas. The question then arises, can the efficiencies of greater beef stocker production from modified IES be utilized with reproductive animals of the cow/calf production system? The purpose of this study was to compare the use of continuous SLS and MIES in a replacement heifer system for western Kansas.
Keywords: available herbage; average daily gain; continuous season-long stocking; first service conception; intensive early stocking; species composition